Determination of the size of the different sepsis categories presenting to a UK teaching hospital emergency department. Issue 1 (21st December 2007) - Majuran, M; Clancy, M
Abstract : Aim: To establish the size of the population of patients presenting to a UK emergency department (ED) with systemic inflammatory response syndrome (SIRS), sepsis, severe sepsis and septic shock and to determine their mortality and length of stay. Setting: Southampton General Hospital Emergency Department, a teaching hospital treating 90 000 patients per annum. Method: A retrospective audit of all patients attending the ED for a 1-month period was undertaken in order to classify them into the different sepsis groups. Length of stay and mortality data were abstracted from the Patient Administration System, a computerised database. Results: 137 (SIRS), 123 (sepsis) and 50 (severe sepsis or septic shock) patients were classified from 5832 new patients attending. The median length of stay was 5, 3 and 7.5 days, respectively, and the mortality was 6.6%, 4.1% and 26%, respectively. The incidence of severe sepsis or septic shock was 30 per 1000 patients admitted. Conclusion: The high incidence of severe sepsis and septic shock with its attendant high mortality and length of stay is highlighted. If the figures are annualised, this would equate to 650 cases of severe sepsis or septic shock, of which 169 would die. The ED is well placed to improve this outcome by earlier detection and the use of goal directed therapy.